EXPLORING JUNIOR HIGH SCHOOL STUDENTS’ FOREIGN LANGUAGE CLASSROOM ANXIETY - Lukman Abdul Jabar; Arini Nurul Hidayati; Yusup Supriyono (Siliwangi University, 2018)
Students’ foreign language classroom anxiety (FLCA), in the last four decades, has been discussed by many researchers regarding to its impact toward students’ learning and achievement. Since “anxiety prevents some people from performing successfully in foreign language learning” (Horwitz et al. (1986 p.125), it is necessary to explore in order to gain success. This present research implements survey study which was conducted among 194 junior high school students in order to find the levels of FLCA, and interview was given to 11 students who are classified as students with High Level of Anxiety in order to explore the factors contributing students’ FLCA. Findings show that there are 63 (32%) students classified in Low Level of Anxiety, 120 (62%) Moderate Level of Anxiety and 11 (6%) High Level of Anxiety, and there are two major factors contributing FLCA which relate to cognitive anxiety and psychological anxiety.